Isolation and identification of nervous necrosis disease virus in wild golden grey mullet (Liza auratus Risso) from iranian coastal waters of caspian sea - Nazari, Alireza (2011)
A study was conducted to determine the etiological agents of serious mortality which occurred in Golden grey mullet (Liza auratus) in Iranian water of south of Caspian Sea. This study was apart of Iranian national research project supported by Iranian Fisheries Research Organization (IFRO). Three hundreds and twelve moribund Grey mullet specimens were collected from 2006 until 2009 in the costal waters of three Northern Provinces of Iran i.e. Gilan, Mazandaran and Golestan. Infected fishes manifested marked clinical signs such as erratic swimming, belly-up at rest, swim bladder distension, exophthalmia and hemorrhages in the skin. Internal organs such as kidney, swim bladder, intestines, eyes and brain were taken for cell culture isolation, serology, and histopathology. Twenty-one VNN-PCR-positive samples obtained from Gilan Province were further examined using cell culture. Cytopathic effects were visualized in SSN-1 cell line which was inoculated with brain and eyes filtrate. The CPEs were characteristic of VNN virus, showing severe cytoplasmic vacuolation and eventually total detachment of the monolayer. Negative staining of infected monolayer cells showed icosahedral particles with a size of 30 nm in diameter. The TEM morphology of these particles was similar to nodavirus particles. IFAT examination of smears prepared from infected cells using MAbs and AAbs against VNNV showed positive results. Histopathological examination of the brain and retina that manifested CPE in cell culture showed necrosis and vacuolation in the brain and retina. TEM examination showed the presence of intracytoplasmic virus particles with 30 nm in diameter in the affected tissues. For confirmation of these results, infectivity study was conducted. Due to difficulty in keeping Grey mullet in aquarium for a long time, an ornamental freshwater fish, guppy (Poecilia reticulata), was chosen and bath challenge using the media of infected cell line. After 15 days post challenge, the fishes showed clinical signs similar to Grey mullet in natural infection. Cell culture isolation, TEM, histopathology and IHC were done for brain and retina from the infected guppy. Similar findings were obtained in infected guppy tissues when compared to naturally infected Grey mullet. In conclusion, with distinguishable clinical signs, TEM and cell culture observation, IFAT and IHC findings from naturally infected Grey mullet and also from experimentally infected guppy, it was thus proved that a viral disease was the causative agent of mortality in the Grey mullet. From the current study it was concluded that Viral Nervous Necrosis Virus was the etiological agent of mortality in Gray mullet in Iranian water of Caspian Sea.